2022
DOI: 10.1177/13621688211072981
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of second-language listening strategy instruction: A meta-analysis

Abstract: Research on the effects of second language (L2) listening strategy instruction (SI) has gained momentum in recent years (e.g. Vandergrift & Tafaghodtari, 2010). However, the reported results have been inconclusive and varied across studies. Synthesizing the results of quantitative research in this domain, the present meta-analysis sought to determine the overall effectiveness of L2 listening SI as well as to examine the extent to which the effectiveness of instruction is likely to vary as a function of a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 83 publications
2
4
0
Order By: Relevance
“…In relation to learner variables, the analyses revealed greater benefit from note taking in FL contexts (g = 0.68) over SL contexts (g = 0.12). This pattern of results aligns with findings from other meta-analyses that explored different SIs such as listening SI (Dalman & Plonsky, 2022) and reading SI (Taylor, 2014). A possible reason for this is that for FL learners taking notes may be more effective for improving learning (Siegel, 2018b) because note taking provides opportunities to optimize learning from the small amount of L2 input that FL learners typically encounter.…”
Section: Moderator Analysissupporting
confidence: 84%
See 2 more Smart Citations
“…In relation to learner variables, the analyses revealed greater benefit from note taking in FL contexts (g = 0.68) over SL contexts (g = 0.12). This pattern of results aligns with findings from other meta-analyses that explored different SIs such as listening SI (Dalman & Plonsky, 2022) and reading SI (Taylor, 2014). A possible reason for this is that for FL learners taking notes may be more effective for improving learning (Siegel, 2018b) because note taking provides opportunities to optimize learning from the small amount of L2 input that FL learners typically encounter.…”
Section: Moderator Analysissupporting
confidence: 84%
“…Kobayashi's (2005) meta-analysis of the encoding effect of note taking on L1 learning revealed that younger learners in primary and secondary schools benefited more from note taking than university students because note taking can compensate for lack of cognitive abilities and skills. However, a recent meta-analysis of listening-strategy instruction on L2 learners' listening performance revealed that older learners tended to benefit more from strategy instruction because they were equipped with superior cognitive and metacognitive abilities (Dalman & Plonsky, 2022). Several metaanalyses examining L2 vocabulary learning also found that older learners tended to make greater learning gains than younger learners (de Vos et al, 2018;Uchihara et al, 2019).…”
Section: Institutional Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…One central topic in second or foreign language (L2) teaching research is enhancing listening comprehension proficiency (Vandergrift, 2004). L2 researchers and practitioners have argued for implementing strategy instruction to promote listening comprehension (Dalman & Plonsky, 2022). However, strategy instruction does not necessarily improve L2 listening comprehension (Milliner & Dimoski, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, strategy instruction does not necessarily improve L2 listening comprehension (Milliner & Dimoski, 2019). Individual differences such as motivation and self‐efficacy can affect listening strategy use (Du & Man, 2022; Xu & Qiu, 2020), which could, in turn, influence the effectiveness of listening strategy instruction (Dalman & Plonsky, 2022; Siegel, 2015). It is of pedagogical importance for listening instructors to know what contributes to listening strategy use.…”
Section: Introductionmentioning
confidence: 99%